1985
DOI: 10.1002/j.1460-2075.1985.tb03768.x
|View full text |Cite
|
Sign up to set email alerts
|

Human p53 cellular tumor antigen: cDNA sequence and expression in COS cells.

Abstract: A 2.5‐kb cDNA clone for human p53 tumor antigen has been isolated. This clone contains the entire coding region including 135 bp upstream of the first ATG. Comparison of the nucleotide sequence of human p53 and mouse p53 demonstrates that the first ATG in human p53 corresponds to the second ATG (codon No. 4) in mouse p53. The human p53 comprises 393 residues and is longer than the mouse p53 due to six additional codons present at the region corresponding to exon 4 of the mouse p53 gene. The DNA sequence homolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(86 citation statements)
references
References 28 publications
5
79
0
2
Order By: Relevance
“…The molecular cloning of the p53 cDNA (Zakut-Houri et al, 1985) allowed a variety of studies to increase our insight into the function of p53 in cell transformation in vitro and in tumorigenesis in vivo. In fact, a number of properties initially attributed to p53 protein, including the ability to immortalize cells (Jenkins et al, 1984) and to transform primary rat embryo ®broblasts in cooperation with ras (Eliyahu et al, 1984;Parada et al, 1984) suggested that it was a dominantly acting oncogene.…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
“…The molecular cloning of the p53 cDNA (Zakut-Houri et al, 1985) allowed a variety of studies to increase our insight into the function of p53 in cell transformation in vitro and in tumorigenesis in vivo. In fact, a number of properties initially attributed to p53 protein, including the ability to immortalize cells (Jenkins et al, 1984) and to transform primary rat embryo ®broblasts in cooperation with ras (Eliyahu et al, 1984;Parada et al, 1984) suggested that it was a dominantly acting oncogene.…”
Section: From Oncogene To Tumour Suppressor Genementioning
confidence: 99%
“…The molecular cloning of the TP53 gene (ZakutHouri et al, 1983;Zakut-Houri et al, 1985) further enabled the understanding of p53 structure and function. Exogenous expression of cloned TP53 was shown to immortalize cells (Jenkins et al, 1984) and endow them with overt tumorigenic potential in mice Eliyahu et al, 1985).…”
Section: Discovery Of Tp53 Mutations In Cancermentioning
confidence: 99%
“…pCMV-E2F-1D413 was made by internal deletion from pCMV-E2F1. pCMV-p53 was made by the insertion of p53 cDNA from php53 (Zakut-Houri et al, 1985) into the pCDNA3. To construct the Gal4-p300 derivatives, pG4-p300 611 ± 1257 , -p300 1302 ± 1572 , -p300 1572 ± 2284 , and -p300 1572 ± 1903 were made by internal detection from pG4-p300 611 ± 2284 , respectively.…”
Section: Transfectionsmentioning
confidence: 99%